2018
DOI: 10.1136/neurintsurg-2018-014260
|View full text |Cite
|
Sign up to set email alerts
|

Direct endovascular thrombectomy and bridging strategies for acute ischemic stroke: a network meta-analysis

Abstract: ObjectivesThe present Bayesian network meta-analysis aimed to compare the various strategies for acute ischemic stroke: direct endovascular thrombectomy within the thrombolysis window in patients with no contraindications to thrombolysis (DEVT); (2) direct endovascular thrombectomy secondary to contraindications to thrombolysis (DEVTc); (3) endovascular thrombectomy in addition to thrombolysis (IVEVT); and (4) thrombolysis without thrombectomy (IVT).MethodsSix electronic databases were searched from their date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
(4 reference statements)
2
25
0
1
Order By: Relevance
“…Finally, BT was not related to delays in groin puncture to recanalization or onset to groin puncture times, compared to BT. 20 Also, we comparatively evaluated outcomes including infarct in new territory and distal embolization complicating MT, as well as time metrics (onset to groin puncture time, groin puncture to reperfusion time), which have not been investigated in prior meta-analyses. They also offer reassurance regarding the concept of distal embolization to other vascular territories due to tPA-related thrombi dissolution, preventing successful MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, BT was not related to delays in groin puncture to recanalization or onset to groin puncture times, compared to BT. 20 Also, we comparatively evaluated outcomes including infarct in new territory and distal embolization complicating MT, as well as time metrics (onset to groin puncture time, groin puncture to reperfusion time), which have not been investigated in prior meta-analyses. They also offer reassurance regarding the concept of distal embolization to other vascular territories due to tPA-related thrombi dissolution, preventing successful MT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Taking into account (1) the poor response of proximal intracranial occlusions to intravenous thrombolysis (IVT) using tissue plasminogen activator (tPA), 11 (2) the substantial treatment effect of MT compared to standard therapy, 12 (3) the consistent improvement in 3-month functional outcomes of both tPA-eligible and tPA-ineligible LVO patients treated with MT, 13 and (4) the potential of IVT pretreatment to delay MT initiation and increase hemorrhagic complications of MT, 14 the utility of IVT pretreatment in LVO patients undergoing MT has been challenged. 15,16 Given that no RCT to date has evaluated the safety and efficacy of bridging therapy (BT; IVT administration prior to MT) compared to direct MT (dMT) and that existing metaanalyses of available observational studies have provided fragmentary and conflicting results to date, [17][18][19][20][21] we performed a comprehensive systematic review and meta-analysis of observational studies and post hoc RCT analyses to investigate the comparative safety and efficacy of BT and dMT in AIS patients with LVO.…”
mentioning
confidence: 99%
“…Maingard et al reported that patients who received bridging therapy had a higher rate of reperfusion and functional independence (mRS 0-2 at 90 days) (21). Contrastingly, a network meta-analysis of 12 studies with a total of 3,161 patients showed that there was no significant difference in good functional outcome at 90 days between direct thrombectomy and bridging therapy (22). However, a comparison of the occurrence of PH between these two treatment options was rarely mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Patients had a median age of 71.5 years (IQR, 61.3-79 years), and 15 (28.8%) were females. The median baseline NIHSS score was 20 (IQR, [16][17][18][19][20][21][22][23]. SMCV− was found in 21 patients (40.4%) (univariate comparisons between SMCV− and SMCV+ are shown in Table S1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Acute ischemic stroke (AIS) is one of the most common strokes that occur in the clinical practice. It is mainly caused by cerebral blood flow disorders, which further leads to ischemic brain necrosis or encephalomalacia[1,2]. For these patients, early therapeutic strategy, especially the widely used revascularization and intravesical therapy, should be used to reduce disability and death rates.…”
Section: Introductionmentioning
confidence: 99%